Development of A Google Site-Based Learning Web to Support Students' Conceptual Understanding of Practical Work Subjects in Grade VIII SMPN 4 Garut - Isyeu Isyeu; A. Wahyudin; Endang Dimyati (Riviera Publishing, 2026)
This study aims to develop a Google Site-based learning website to improve the conceptual understanding of 30 students in the Crafts subject of class VIII at SMPN 4 Garut. The research method used is Research and Development (R&D) with the ADDIE model, consisting of the stages of analysis, design, development, implementation, and evaluation. The product developed is a digital learning media containing materials, images, video tutorials, practice questions, and online evaluations that can be accessed flexibly through various devices. The validation results by material experts and media experts show that the learning media is in the very feasible category with a percentage of ?90%. The results of the effectiveness test show an increase in student learning outcomes, as indicated by an increase in the average pretest score of 60.33 to 82.67 in the posttest. The results of the N-Gain test obtained a value of 0.65 (medium category), with the distribution of increases in the high category of 33%, medium 57%, and low 10%. Furthermore, the paired samples t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest results. Student responses to the use of the media were also positive. Therefore, it can be concluded that the Google Site-based learning website developed is valid, practical, and effective in improving students' conceptual understanding of the Crafts subject.